Are hip fracture patients with high or low body mass index at higher risk of missed care? A cohort study - Nanna Sofie Astrup Pedersen; Inger Mechlenburg; Pia Kjær kristensen (Wiley, 2023)
Abstract Aim To examine whether patients' body mass index is associated with missed hip fracture care consistent with national guideline‐recommended care. Design A nationwide, population‐based cohort study using prospectively collected data from the Danish Multidisciplinary Hip Fracture Registry. Methods The study population consisted of 39,835 patients ≥65 years admitted with a hip fracture and discharged between 1st of January 2012 and 29th of November 2017. National guideline‐recommended care consists of preoperative optimization, early surgery, mobilization within 24 h, basic mobility assessment, nutrition screening, post‐discharge rehabilitation program, and osteoporotic and fall prophylaxis. We used binomial regression to estimate the relative risk for the fulfilment of the individual measures with 95% confidence interval. Multiple imputation method was applied to handle missing values of body mass index. Results The overall fulfilment of the individual measures ranged from 43% for pre‐operative optimization to 95% for receiving a post‐discharge rehabilitation program. The obese patients had a lower fulfilment of surgery within 36 h compared to patients with normal weight. No differences in fulfilment of the other measures were found. However, patients with missing data on body mass index had the highest risk of missed care. In conclusion, patients with missing BMI values had the highest risk of missed care. The obese patients had a slightly higher risk of long waiting times for surgery than normal‐weighted patients. No Patient or Public Contribution This study was done based on population‐based data from medical registries and data was analysed by the authors only.